Agentes de su propio juego - Anderson Roos, Jeanine (2024)
Play has been underrepresented in studies of Andean communities, together with the children who are its protagonists. This article, part of a larger ethnographic study, reviews and analyzes manifestations of play in rural localities of the province of Yauyos. It aims to interpret the role of play and reevaluate its importance. With the support of numerous descriptions of places of play, toys, the actors, their motivations and relations, it examines the presence of a “rhetoric of progress” and a “rhetoric of power” in Yauyos children’s play. Play constitutes a dominion where the agency of boys, girls, and adolescents emerges with special clarity. The result is the structuring of a child’s society that incorporates alliances and cooperation as well as conflicts and exclusions.